THE RELATIONSHIP BETWEEN WORKLOAD AND WORK STRESS AMONG EMPLOYEES AT PT EVERBRIGHT RANTAUPRAPAT BRANCH (Case Study: Jalan Adam Malik, Darat, South Rantau District) - Henny Pratiwi; Nurfadillah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to determine “The Relationship Between Workload and Work Stress Among Employees at PT Everbright Rantauparapat Branch.” Workload was measured through indicators of targets to be achieved, working conditions, use of working time, work standards, and work stress was measured through indicators of task demands, role demands, organizational leadership, and interpersonal demands. The research population consisted of 36 people with a saturated sampling technique. Primary data were obtained from Likert-scale questionnaires. Based on the results of data analysis conducted, it was found that the research data met the normality assumption, as indicated by a significant value of 0.087, meaning that the data were normally distributed. In addition, the results of the linearity test showed a significance value of deviation from linearity of 0.500, which means that the relationship between workload and work stress is linear. Furthermore, the results of the simple linear regression test showed that there was a relationship between workload and work stress with a result of 0.534, meaning that there is a fairly strong relationship between workload and work stress.